Outcomes and Impacts of 10-Year HTA Implementation in Taiwan. (28th February 2019) - Kao, Kai-Ling; Huang, Li-Ying; Wu, Yen-Hui; Gau, Churn-Shiouh
Abstract : Objectives: In 2007, Taiwan began conducting health technology assessments (HTA) to support the National Health Insurance Administration (NHIA) in its reimbursement decisions for drugs, medical devices, and medical services. Methods: In this study, the development, missions, and procedures of the implementation of HTA in Taiwan are briefly introduced. Moreover, the value of HTA is examined by reviewing the outcomes and impacts of recent HTA-related research projects, which are classified into five categories: (i) pharmaceutical products, (ii) medical procedures, (iii) medical devices, (iv) health policy, and (v) social care. Results: Overall, the 10-year implementation of HTA has not only supported the government's decision making but also enhanced patient care. Furthermore, patient evidence has been highlighted, and patient care pathways have been transformed through patient involvement in HTA. Conclusions: In conclusion, HTA's value has been determined by both government and social aspects in Taiwan.